Unlocking the training process: how different training tasks shape the physiology and biomechanics of professional futsal players - Serrano, Carlos; Ferraz, António; Ribeiro, João Nuno; Ibañez, Enrique; Travassos, Bruno (Frontiers in Sports and Active Living, 2025)
IntroductionDespite the characterization of the physical and technical tactical demands of futsal SSCGs, there remains a need to better understand the physiological and biomechanical loads of each training task to determine its workload during training sessions further. The present study aims to analyze and classify the physiological and biomechanical demands of different futsal training tasks to enhance the understanding of these demands and their implications for elite futsal players’ performance.MethodsConducted over three seasons with a professional futsal team, this study systematically categorized training exercises into six task types: introductory, analytical, mid-court, ¾ court, full-court, and superiority/inferiority tasks. The WIMU PRO™ device was used to monitor physiological and biomechanical metrics and to assess how variations in task type influence them.ResultsSuperiority/inferiority tasks, followed by full-court tasks, showed significantly higher physiological and biomechanical loads compared with introductory, analytical, and mid-court tasks. These differences (p ≤ 0.05) were associated with higher values of average heart rate, total distance covered, and high-speed running per minute for the physiological load, as well as a greater number of accelerations, decelerations, and player load per minute for the biomechanical load.DiscussionA visual four-quadrant effort assessment provided insights into the contribution of each task category through its specific load distribution, revealing significant variations associated with player numbers, field dimensions, and task objectives. These findings suggest that specific task configurations can be strategically used to optimize training outcomes by aligning physical demands with coaching objectives.